2018
DOI: 10.1038/s41598-018-34029-y
|View full text |Cite
|
Sign up to set email alerts
|

Formation of neocortical memory circuits for unattended written word forms: neuromagnetic evidence

Abstract: To master linguistic communication, humans must acquire large vocabularies quickly and effortlessly. Efficient word learning might be facilitated by the ability to rapidly acquire novel word forms even outside the focus of attention, occurring within minutes of repetitive exposure and suggesting fast and automatic lexicon acquisition. However, this phenomenon has been studied in the auditory modality only, and it is unknown whether similar mechanisms also exist in the visual domain. We tested this by presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
6
10
0
Order By: Relevance
“…Furthermore, it shows that novel word learning processes can be rather automatic, with the lexico-semantic processing of stimuli accessed and modulated even during a task in which no response is required from readers. Moreover, these findings extend previous results found in this strand of research, which have shown the rapid and automatic acquisition of memory traces for novel written word-forms after their fully unattended, parafoveal exposure (Partanen et al, 2018). In this sense, word learning effects have been found even when reader’s attention is directed to different stimuli.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, it shows that novel word learning processes can be rather automatic, with the lexico-semantic processing of stimuli accessed and modulated even during a task in which no response is required from readers. Moreover, these findings extend previous results found in this strand of research, which have shown the rapid and automatic acquisition of memory traces for novel written word-forms after their fully unattended, parafoveal exposure (Partanen et al, 2018). In this sense, word learning effects have been found even when reader’s attention is directed to different stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, magneto-and electroencephalography methodologies, able to track online-processing changes in brain activity, are probably much more sensitive to assess novel word learning and, particularly, the nature of the neurophysiological mechanisms underlying a specific training with the orthographic or both the orthographic and semantic features of novel words. Regarding the effect of single orthographic training, rather few MEG/EEG studies are focused on neural dynamics during the acquisition of novel surface word-forms, with substantial methodological differences and inconsistent findings among them (Bermúdez-Margaretto et al, 2015, 2018; Partanen et al, 2018). For instance, in a recent MEG study, Partanen et al (2018) found that massive (~100 repetitions) and unattended, parafoveal exposure to novel written word-forms caused an increase in the early brain activity, at around 100 ms post-stimulus onset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to a substantial amount of ERP research in spoken language, focused on rapid learning of pure phonological word-forms, the evidence regarding the putative neurophysiological mechanisms underlying the acquisition of orthographic word-forms is rather limited. The vast majority of studies in this strand of research (including the ones listed above) combined training in both the orthography and the meaning of new words [ 8 , 14 , 76 , 82 ], whereas only few of them evaluated the brain dynamics underlying purely orthographic learning as such (e.g., [ 11 , 13 , 80 ]). However, the underlying neural mechanisms for the acquisition of a novel surface form per se and the meaning attached to it are likely dissociable, with one related to the analysis of visual features and the orthographic recognition of the surface form and the other related to the access of its associated concept [ 23 , 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while EE seems to benefit from an overnight consolidation stage, learning via fast mapping does not trigger overnight changes in brain representations (Merhav et al, 2015). Moreover, even passive exposure to unattended novel word forms presented repeatedly outside of any task or context leads to immediate changes in the brain responses, indicative of a novel memory trace build-up in the perisylvian neocortex (Kimppa et al, 2015, 2016; Partanen et al, 2017, 2018), provided the exposure is intensive enough (dozens to hundreds of repetitions). Such different brain signatures of the two learning strategies in themselves support (partially) different mechanisms underpinning them and may thus explain diverging learning dynamics and efficiency.…”
mentioning
confidence: 99%